Critical infrastructure lifelines and the politics of anthropocentric resilience. Issue 3 (2nd September 2017) - Coaffee, Jon; Clarke, Jonathan
Abstract: The discourse of resilience has increasingly been utilised to advance the political prioritisation of enhanced security and to extend the performance of risk management in the Anthropocene. This has been notably advanced through integrated approaches that engage with uncertainty, complexity and volatility in order to survive and thrive in the future. Within this context, and drawing on findings from a number of EU-wide research projects tasked with operationalising critical infrastructure resilience, this paper provides a much-needed assessment of how resilience ideas are shaping how critical infrastructure providers and operators deal with complex risks to 'lifeline' systems and networks, whilst also illuminating the tensions elicited in the paradigm shift from protective-based risk management towards adaptive-based resilience. In doing so, we also draw attention to the implications of this transition for organisational governance and for the political ecologies of the Anthropocene that calls for more holistic, adaptable and equitable ways of assessing and working with risk across multiple systems, networks and scales.